Mentoring Improves the Labor-Market Prospects of Disadvantaged Adolescents - Sven Resnjanskij; Jens Ruhose; Simon Wiederhold; Ludger Woessmann (CESifo Forum, 2021)
How can the labor-market prospects of school-attending adolescents from disadvantaged families be improved? One possible approach is the use of mentoring programs that assign adolescents a mentor who can provide them with support that their family environment is not able to provide. But do such programs really help? Testing this empirically is difficult because it is unclear how these adolescents would have developed without participating in the mentoring program, since available datasets generally do not include a convincing control group of similarly disadvantaged youths. To overcome this limitation, we randomized participation in a large German mentoring program, exploiting the fact that the program was oversubscribed, i.e., had more applicants than available slots. Due to the random assignment, the adolescents who did not participate in the program provide a compelling control group for the participants. We find that the mentoring program significantly improves an index of labor-market prospects for eighth- and ninth-graders from severely disadvantaged families one year after program start. The positive effects are present for all three components of the index, which measure cognitive (math grade), non-cognitive (patience and social skills) and motivational (labor-market orientation) aspects. For disadvantaged adolescents, the expected income benefits from program participation greatly exceed program costs. In contrast, the program has no positive effects for adolescents from less disadvantaged families. The results suggest that mentoring works when it compensates for a lack of family support.
Keywords: 330